Reading comprehension in elementary levels: a Systematic literature review - Triana, Putri Meinita; Pradana, Agrissto Bintang Aji; Wardana, Aditia Eska (Jurnal Bidang Pendidikan Dasar, 2024)
Reading comprehension is currently crucial to children's knowledge acquisition. As a result, several study have been conducted to improve their reading comprehension skills. Furthermore, the purpose of this research is to investigate how it is enhanced in primary schools and ditermine current trends in the field. This is a systematic literature review that employed ERIC, PubMed, and Science Direct as databases. It gathered articles published in 2023. Article filtration method employed PRISMA stages. Out of 162 articles retrieved, 9 articles were considered relevant. The results stated that instructors use a variety of approaches, strategies, and school programs to increase students' reading comprehension. Strategies and media still remains dominant in this field and they preferably integrate technology into the teachig and learning process.